Mathematical Literacy Ability and Mathematical Disposition on Team Assisted Individualization Learning with RME Approach and Recitation - Lestari, Septi Dini; Kartono, Kartono; Mulyono, Mulyono (Unnes Journal of Mathematics Education Research, 2019)
This study aims to (1) determine the quality of Team Assisted Individualization learning with RME approach recitation on students' mathematical literacy abilities; and (2) describe the mathematical literacy abilities viewed from students' mathematical dispositions. This study applied a mixed method research type with concurrent embedded designs. Subjects in this study were determined based on the score of the mathematical disposition questionnaire of students in grade VIIB SMP N 40 Semarang in the academic year of 2017/ 2018. The data collection techniques were observation, tests and interviews. The results of the study showed that (1) Team Assisted Individualization learning with RME approach recitation has good quality; (2) students with high mathematical dispositions master the components of communication, mathematising, reasoning & argument, and devising strategies very well, the components of using symbolic, formal, and technical language and operation were well mastered, and the other two components are quite well mastered. Students with medium mathematical dispositions mastering well the components of communicaton, mathematising, and devising strategies for solving problems, the components of reasoning and argumentation and using symbolic, formal, and technical language and operation were mastered quite well but they have not been able to master the other two components. Students with low mathematical dispositions can only mastered three components quite well, they are communication, mathematising, and mathematics tools, while the other four have not been able to be mastered